Citizens' assessment of the information quality of e-government websites in Pakistan. Issue 3 (17th October 2019) - Rasool, Tayyba; Warraich, Nosheen Fatima; Rorissa, Abebe
Abstract : Purpose: E-government websites/portals are effective modes of communication between governments and citizens. The information quality (IQ) of these websites/portals is of vital importance and, hence, is worth assessing, to ensure their effectiveness. This study aims to assess the IQ dimensions of e-government websites/portals in Pakistan and also evaluate the most significant IQ indicators. Design/methodology/approach: This study used a quantitative research method based on a survey. The data were collected from a sample of young citizens, and a questionnaire was adopted from a previous study by Kandari, et al . (2011 ) with minor changes to reflect the local context. Findings: The findings revealed that out of 20 IQ indicators, 14 were rated 4 or 5 on a five-point Likert scale, indicating a reasonably high IQ for Pakistani e-government websites/portals. Value-added, "accessibility" and "objectivity" were the top three indicators, while timeliness, ease of operation and advertisement were the least rated indicators, suggesting that these need to be addressed. The findings of the study also revealed that IQ indicators are not affected by the different age groups of citizens. Research limitations/implications: The focus of this study was limited to university students to understand their perceptions about IQ indicators of e-government websites in Pakistan, and the results can only be generalized to young Pakistani citizens and the developing countries with a similar context. Practical implications: This study could provide some guidance to policy makers and websites designers in the development of e-government websites according to users' needs and identifying the ways to regularly maintain and update these websites. Originality/value: This study provides an understanding of the IQ of Pakistani e-government websites from the citizens' perspective. It attempts to fill that gap and produce findings that could assist in making informed policy decisions.